Prevalence of Bartonella species infections in cats in Southern Germany. (1st April 2017) - Bergmann, M.; Englert, T.; Stuetzer, B.; Hawley, J. R.; Lappin, M. R.; Hartmann, K.
Abstract : Bartonella species are zoonotic pathogens, and infections in cats are common. However, prevalence in cats in Southern Germany is still unknown. Therefore, prevalence of Bartonella species DNA in blood of 479 Southern German cats was determined using a previously published conventional PCR targeting a fragment of the 16S‐23S rRNA intergenic spacer region. Associations between Bartonella bacteraemia, housing conditions, feline immunodeficiency virus (FIV) and feline leukaemia virus (FeLV) status, including progressive, regressive and abortive FeLV infection, were evaluated using Fisher's exact test. Prevalence of Bartonella species bacteraemia was 2.5 per cent (12/479; CI 0.01–0.04 per cent). Bartonella henselae DNA was amplified in 11 of the 12 cats. One cat was positive for Bartonella clarridgeiae DNA. Of the infected cats, 2/12 cats were ill; 6/12 cats had thrombocytopenia. There was a significantly higher risk of Bartonella species infection in young and shelter cats, but not in FIV‐infected or FeLV‐infected cats. Prevalence of Bartonella species bacteraemia is low in Southern German cats, but there is still a risk of zoonotic transmission associated with ownership of young cats. Most of the infected cats did not show clinical signs. Thrombocytopenia was common in Bartonella species‐infected cats and further studies are required to define its clinical relevance.